Salamanders in Regeneration Research Methods and Protocols - Kumar, Anoop.; Kumar, Anoop.; Simon, András.; Simon, András. (Methods in Molecular Biology,, 2015)
This detailed volume focuses on best practices and conditions for maintaining the most commonly used salamander species in the laboratory. Salamanders in Regeneration Research: Methods and Protocols guides readers through experimental manipulations in vivo and in vitro, respectively. With methods on targeting a wide variety of structures, ranging from the limb to the heart and to the brain, and methods for studying genetically modified organisms and tools for mining in the genomic databases. Written in the highly successful Methods in Molecular Biology series format, chapters include introduction to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and up-to-date, Salamanders in Regeneration Research: Methods and Protocols provides a comprehensive collection of methods chapters.